Diagnosis and Management of New-Onset Central Diabetes Insipidus in Critically Ill Children Varies between Pediatric Critical Care Medicine and Pediatric Endocrinology Clinicians - Hunter, R. Brandon; Guzman, Herodes; Winters, Jessica; Lord, Katherine; Kirschen, Matthew; Srinivasan, Vijay (Journal of Pediatric Intensive Care, 2022)
The diagnosis and management of central diabetes insipidus in critically ill children is not standardized. Our objective was to characterize differences between Pediatric Critical Care Medicine (PCCM) and Pediatric Endocrinology (PE) clinicians in the diagnosis and management of new-onset CDI in the pediatric intensive care unit. We also sought to characterize knowledge gaps among general pediatrics (GP) residents. This is a scenario-based survey to assess patterns of diagnosis and management of new-onset CDI that was distributed to PCCM, PE, and GP clinicians who work in a quaternary care urban children's hospital. Of 275 PCCM, PE, and GP clinicians surveyed, 158 (57%) responded. More PCCM than PE clinicians relied on serum sodium levels (96 vs. 75%, p <0.01) and more PE than PCCM clinicians relied on serum osmolality (91 vs. 40%, p < .001) for diagnosis. Fewer PCCM than PE clinicians favored restricting IV fluids to two-thirds maintenance rate (4 vs. 37%, p <0.001). More PCCM than PE clinicians favored a starting dose of 0.5 milli-units/kg/h for IV vasopressin infusion (76 vs. 53%, p = 0.048). More PCCM clinicians than PE clinicians favored titrating the IV vasopressin infusion every 20 minutes (24 vs. 2%, p = 0.02), whereas more PE clinicians than PCCM clinicians favored titration every 60 minutes (38 vs. 14%, p = 0.03). GP residents earlier in training had greater self-reported gaps in knowledge. We observed substantial variability in the diagnosis and management of new-onset CDI in critically ill children among PCCM, PE, and GP clinicians. There is a need for greater standardization in care of these patients.
Keywords: pediatrics; critical care; endocrinology; diabetes insipidus; clinical care